Modus Operandi: Continuously Transforming And Renewing Action In Architectural Design Studio (EAAE Annual Conference Proceedings, 2023)
In the plurality of the contemporary world, the content and limits of architects’ knowledge and skills are in an indefinable expansion. A fundamental problem is the difficulty of determining the essential knowledge and skills provided to the architectural student within the framework of education and whether the foundation provided by education can provide a structure suitable for the integration of new, non-scoped knowledge and skills into professional practice.